Synthesis and Characterization of Lanthanide(III) 7-[(Amino(4-Hydroxyphenyl) Acetyl) Amino]-3-methyl-8-oxo Complexes - PINGALKAR, S.R.; DESHPANDE, M.N. (Asian Journal of Chemistry, 2010)
Lanthanide(III) complexes of 7-[(amino(4-hydroxyphenyl) acetyl) amino]-3-methyl-8-oxo (AHAAMO) monohydrate with the general composition [Ln(L2)(H2O)2]CI (where Ln = La, Ce, Pr, Nd, Sm, Gd., Tb or Dy) have been prepared and characterised by the elemental analysis, conductivity measurement, UV-visible, IR, NMR spectra, X-ray diffraction studies, magnetic susceptibility and thermal studies. Infrared studies of these complexes reveal that AHAAMO acts as tetradentate ligand and coordinate through nitrogen and oxygen.